Transmetalation from Magnesium–NHCs—Convenient Synthesis of Chelating π-Acidic NHC Complexes - Messelberger, Julian; Grünwald, Annette; Stegner, Philipp; Senft, Laura; Heinemann, Frank Wilhelm; Munz, Dominik (Inorganics, 2019)
The synthesis of chelating N-heterocyclic carbene (NHC) complexes with considerable -acceptor properties can be a challenging task. This is due to the dimerization of free carbene ligands, the moisture sensitivity of reaction intermediates or reagents, and challenges associated with the workup procedure. Herein, we report a general route using transmetalation from magnesium-NHCs. Notably, this route gives access to transition-metal complexes in quantitative conversion without the formation of byproducts. It therefore produces transition-metal complexes outperforming the conventional routes based on free or lithium-coordinated carbene, silver complexes, or in situ metalation in dimethyl sulfoxide (DMSO). We therefore propose transmetalation from magnesium-NHCs as a convenient and general route to obtain NHC complexes.
CRIS-Team WoS Importer:2019-06-28